2011
DOI: 10.1007/s00423-011-0863-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy as a teaching operation: comparison of outcome between residents and attending surgeons in 1,747 patients

Abstract: Purpose Standardized surgical training is increasingly confronted with the public demand for high quality of surgical care in modern teaching hospitals. The aim of this study was to compare the results of laparoscopic cholecystectomy (LC) performed by resident surgeons (RS) and attending surgeons (AS). Methods In this retrospective review of prospectively collected data 1,747 LC were performed in a community hospital between 1999 and 2009. Seven hundred seventy operations were performed by RS. Parameters analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 28 publications
4
25
0
1
Order By: Relevance
“…Patient outcomes after surgical procedures performed by surgical trainees have been previously studied. A number of studies have reported that operative times tend to be longer with the participation of trainees, which is consistent with the results of this trial .…”
Section: Discussionsupporting
confidence: 91%
“…Patient outcomes after surgical procedures performed by surgical trainees have been previously studied. A number of studies have reported that operative times tend to be longer with the participation of trainees, which is consistent with the results of this trial .…”
Section: Discussionsupporting
confidence: 91%
“…32 However, another study, pertaining to the field of general surgery, showed that resident involvement in laparoscopic cholecystectomy was associated with a shorter length of hospital stay, lower morbidity, and comparable overall mortality. 19 Our study concludes, through a robust statistical analysis and a sufficiently large sample size drawn from a large, multi-center database of hospitals throughout the United States, that resident participation in surgery does not negatively affect clinical outcomes, in terms of morbidity and mortality. This is despite the fact that residents were typically involved in more complex cases, as evidenced by the fact that the resident involvement subgroup had higher work value units and a higher percentage of emergency cases, infected surgical wounds preoperatively, perioperative blood transfusions, previous surgical interventions within 30 days, diabetes, sepsis, abnormal preoperative laboratory values, and disseminated cancer.…”
Section: Discussionmentioning
confidence: 78%
“…[6][7][8][9][10][11][12][13][14][15] In addition, although many patients prefer to receive their care at teaching hospitals, some patients are reluctant to have residents involved in their surgical care. [16][17][18] No studies have evaluated the effect of resident involvement across all surgical specialties regardless of the type of the procedure or specialty, although published research has already explored the effect of resident involvement in surgery on operative time 6,7,19 and on mortality and morbidity in specific surgical specialties. 8,[11][12][13][20][21][22][23] Different studies reported on the effect of surgical resident involvement on a specific group or type of surgical procedures.…”
mentioning
confidence: 99%
“…They showed that supervised LC performed by trainees does not increase surgical morbidity and does not compromise surgical outcome (LE4). Fahrner et al [299] showed that with adequate training, supervision and correct patient selection, surgical residents can perform LC with results comparable to those of experienced surgeons. The only statistically significant difference was the operative time (LE3).…”
Section: Statementmentioning
confidence: 93%